2014
DOI: 10.1002/jcb.24839
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α (HNF4α) in Coordination With Retinoic Acid Receptors Increases all‐trans‐Retinoic Acid‐Dependent CYP26A1 Gene Expression in HepG2 Human Hepatocytes

Abstract: CYP26A1 expression is very highly induced by retinoic acid (RA) in the liver, compared to most other tissues, suggesting that a liver-enriched factor may be required for its physiological transcriptional response. HNF4α is a highly conserved liver-specific/enriched member of nuclear receptor superfamily. In this study, we hypothesized that HNF4α and RARs may cooperate in an RA-dependent manner to induce a high level of CYP26A1 expression in liver cells. Partial inhibition of endogenous HNF4α by siRNA reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…RA can also signal through peroxisome proliferator-activating receptor beta (PPAR- β ) when it forms a heterodimer with RXR, which may be important for lipid metabolism and glucose homeostasis [ 1 ]. In addition, chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII) [ 32 ] and hepatocyte nuclear factor 4 (HNF-4) [ 33 ] receptors can forms a heterodimer with RXR and become low-affinity retinoic acid receptors. Similar to PPAR- β , their signals are important for lipid metabolism and glucose homeostasis [ 32 ].…”
Section: Ra Metabolism and Signalingmentioning
confidence: 99%
“…RA can also signal through peroxisome proliferator-activating receptor beta (PPAR- β ) when it forms a heterodimer with RXR, which may be important for lipid metabolism and glucose homeostasis [ 1 ]. In addition, chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII) [ 32 ] and hepatocyte nuclear factor 4 (HNF-4) [ 33 ] receptors can forms a heterodimer with RXR and become low-affinity retinoic acid receptors. Similar to PPAR- β , their signals are important for lipid metabolism and glucose homeostasis [ 32 ].…”
Section: Ra Metabolism and Signalingmentioning
confidence: 99%
“…Of interest, studies have shown that retinoic acid, ginsenoside Rg3 and 18β-glycyrrhetinic acid can induce hepatic differentiation at least partly via modulation of HNF 4α [41][42][43]. These findings suggest that it should be possible to induce differentiation in HCC.…”
Section: Hnf 4α As a Potential Therapeutic Target For Hccmentioning
confidence: 99%
“…HNF4α plays important roles in lipid and glucose metabolism, and in the catabolism of xenobiotics and drugs, particularly by CYP450 (Hwang‐Verslues & Sladek, ; Jover, Bort, Gomez‐Lechon, & Castell, ). Zolfaghari and Ross found that HNF4α combined with retinoic acid enhanced expression of CYP26A1 (Zolfaghari & Ross, ). HNF6 can relieve hepatic apoptosis and impede the progression of liver disease, and has distinct mechanisms to enhance hepatic protection (Wang, ).…”
Section: Innovationsmentioning
confidence: 99%
“…These transcription factors constitute a complex regulatory network that accurately controls liver development and hepatocyte function(Bingle, Hackett, Moxley, Longmore, & Gitlin, 1995;Colclough, Bellanne-Chantelot, Saint-Martin, Flanagan, & Ellard, 2013;Hajarnis et al, 2015).With the help of HNFs, such as HNF4α, HNF6 and HNF1α, in vitro models provide a more accurate determination of DMEs.HNF4α plays important roles in lipid and glucose metabolism, and in the catabolism of xenobiotics and drugs, particularly by CYP450(Hwang-Verslues & Sladek, 2010;Jover, Bort, Gomez-Lechon, & Castell, 2001). Zolfaghari and Ross found that HNF4α combined with retinoic acid enhanced expression of CYP26A1(Zolfaghari & Ross, 2014). HNF6 can relieve hepatic apoptosis and impede the progression of liver disease, and has distinct mechanisms to enhance hepatic…”
mentioning
confidence: 99%